Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2011
DOI: 10.1007/s12038-011-9096-z
|View full text |Cite
|
Sign up to set email alerts
|

Nucleic acid therapy for lifespan prolongation: Present and future

Abstract: Lifespan prolongation is a common desire of the human race. With advances in biotechnology, the mechanism of aging has been gradually unraveled, laying the theoretical basis of nucleic acid therapy for lifespan prolongation. Regretfully, clinically applicable interventions do not exist without the efforts of converting theory into action, and it is the latter that has been far from adequately addressed at the moment. This was demonstrated by a database search on PubMed and Web of Science, from which only seven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(7 citation statements)
references
References 52 publications
0
5
0
Order By: Relevance
“…To enhance the efficiency in loading nucleic acids, graphene-based carriers are often functionalized with polycations. One of the widely used polycations is PEI [90] , which on one hand can interact with negatively charged nucleic acids [91] , [92] , [93] , [94] , [95] and on the other hand can provide active groups for further functionalization to enhance the transfection efficiency and the tissue targeting capacity. This is demonstrated by an earlier study [96] , which has functionalized GO with PEI as a gene carrier and has found that the PEI moieties enable the carrier to complex with nucleic acids and to promote the adhesion of the complex to the plasma membrane for enhanced cellular uptake [96] .…”
Section: Design Of Graphene-based Materials For Bioactive Agent Deliverymentioning
confidence: 99%
“…To enhance the efficiency in loading nucleic acids, graphene-based carriers are often functionalized with polycations. One of the widely used polycations is PEI [90] , which on one hand can interact with negatively charged nucleic acids [91] , [92] , [93] , [94] , [95] and on the other hand can provide active groups for further functionalization to enhance the transfection efficiency and the tissue targeting capacity. This is demonstrated by an earlier study [96] , which has functionalized GO with PEI as a gene carrier and has found that the PEI moieties enable the carrier to complex with nucleic acids and to promote the adhesion of the complex to the plasma membrane for enhanced cellular uptake [96] .…”
Section: Design Of Graphene-based Materials For Bioactive Agent Deliverymentioning
confidence: 99%
“…DNA nanotechnology involves the development of programmable nanoscale building materials 63–67 . These materials are easy to assemble to readily attain the desired shapes 68–71 .…”
Section: Summary and Outlooksmentioning
confidence: 99%
“…Contrary to the delivery of chemical drugs, in which the intervention will still be therapeutic even if the carrier fails to be internalized into cells but simply releases the payload outside, gene therapy is possible only when cellular internalization of the delivered gene is successful. 58 60 As far as cellular uptake is concerned, the size and zeta potential of the nanoparticles are two important determining factors. A small size can be achieved by surface passivation or functionalization to enhance the colloidal stability of UCNPs.…”
Section: Molecular Design Of Ucnps As Gene Carriersmentioning
confidence: 99%